ANALISIS SISTEM PENGENDALIAN INTERNAL PENGELUARAN KAS PADA PT. MYCONSULTING BUSINESS ASIA - Lucia Jessica Kartikasari (2021)
This study aims to determine how the implementation of the internal control system for cash disbursements at PT. Myconsulting Business Asia and find out whether the implementation of the internal control system for cash disbursements at PT. Myconsulting Business Asia has been running effectively. The theory used in this study is the theory of Mulyadi. This study uses qualitative research methods, with an interpretive paradigm and a phenomenological approach. Data collection techniques in this study were using interviews and documentation. The results of this study indicate that overall PT. Myconsulting Business Asia has implemented an effective cash disbursement internal control system in accordance with the elements of the internal control system according to Mulyadi. However, there are weaknesses in the implementation of the internal control system, namely there are dual tasks that result in human errors in the company's cash disbursement activities, the implementation of several healthy practices such as job rotation, obligation to take leave for employees, the establishment of the company's internal supervisory unit, the use of paid stamps to be affixed to basic documents along with supporting documents for cash disbursements transactions, and have not implemented the imprest system as a method of recording petty cash funds. Then, the cash in the company, the cash on the way, and the cashier at the company have not been insured.